A Comparison of the Two-Minute Walk Test (2MWT) and Comprehensive High-level Activity Mobility Predictor (CHAMP) in People with a Leg Prosthesis. (May 2022) - Gailey, Robert S.; Gaunaurd, Ignacio; Morgan, Sara J.; Kristal, Anat; Balkman, Geoffrey S.; Newton, Eavey M; Palomo, Jose J; Shay, Kevin M; Salem, Rana; Hafner, Brian J.
Objective: To determine if the two-minute walk test (2MWT) could serve as an alternative measure of high-level mobility in lower limb prosthesis users when circumstances preclude administration of the Comprehensive High-level Activity Mobility Predictor (CHAMP). Design: Cross-sectional study. Setting: Indoor recreational athletic field and gymnasium Subjects: Fifty-eight adult lower limb prosthesis users with unilateral or bilateral lower limb amputation who participate in recreational athletic activities. Intervention: N/A Main Measures: The 2MWT and CHAMP while using their preferred prosthesis(es) on an indoor artificial athletic field or hardwood gymnasium floor. Results: Thirty-nine men and nineteen women with a median age of 38.3 years participated in the study. Most participants experienced amputation(s) due to trauma (62%) or tumor (10%) and were generally higher functioning (K4 (91.4%) and K3 (8.6%)). The median (range) score for the CHAMP was 23.0 points (1.5–33.5) and the mean ± standard deviation (range) 2MWT distance walked was 188.6 ± 33.9 m (100.2–254.3 m). The CHAMP demonstrated a strong positive relationship with 2MWT (r = 0.83, p < 0.001). The 2MWT distance predicted 70% of the variance in CHAMP score. Conclusions: Although the 2MWT does not test multi-directional agility like the CHAMP, they were found to be highly correlated. If space is limited, the two-minute walk test can serve as an alternative measure for assessing high-level mobility capabilities in lower limb prosthesis users.